ผลการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษา เพื่อส่งเสริมจิตนิสัยทางสะเต็ม: Effcet of Learning the Stem Education to Enhance the Stem Habits of Mind - Karunram, Anongnat; Meesawat ื์Nataporn (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research focused on STEM teaching in Thermal energy and state of matter, Eco-lodge and Water treatment contents for enhances STEM habits of mind and characteristic STEM habits of mind with learning achievement in grade 7 students. The sample in this research were 29 student in grade 7 at Muangtalungpittayasan School. Four types of research instruments were (1) experimental tools: three STEM Education lesson plans for enhance STEM habits of mind; (2) evaluation tools: the STEM habits of mind evaluation form, achievement test and an interview assessment form. Descriptive statistics are used to describe a variables for a sample of data, the mean, standard deviation, a t-test for dependent sample and ANOVA. The non-numeric information were analyzed by content analysis. The results indicate that: After the programs, the learning achievement was significantly improved at a level of .05 This programs was able to enhance STEM habits of mind. The results showed that the STEM habits of mind in student were higher than average. The results showed that content analysis of learning activity transcribed and interviewed revealed that the STEM habits of mind includes six aspect, 1) Curiosity 2) Carefully Making decision 3) Integrative thinking 4) Recognizing cause and effect 5) Communicative ability and 6) Innovative ability.